Free vibration characteristics of multi-core sandwich composite beams: Experimental and numerical investigation. Issue 9 (November 2021) - Selvaraj, Rajeshkumar; Gupta, Kamesh; Singh, Shubham Kumar; Patel, Ankur; Ramamoorthy, Manoharan
This study investigates the free vibration responses of laminated composite sandwich beam with multi-cores using experimental and numerical methods. The laminated composite face sheets are made by using hand layup method. An experimental modal test has been carried for different configurations of multi-core sandwich beams under different end conditions. The single-core and multi-core sandwich beams has been modeled and the natural frequencies of sandwich beams are determined using ANSYS software. The numerical model is verified by comparing the obtained natural frequencies with experimental results. The numerical and experimental results indicate that the multi-core sandwich beam greatly influences the structural stiffness compared with single-core sandwich beam under different end conditions. Furthermore, the influence of several parameters such as the end conditions, thickness of the core layer, and stacking sequence on the natural frequencies of the various configurations of the multi-core sandwich beams are presented.